2010
DOI: 10.1037/a0019038
|View full text |Cite
|
Sign up to set email alerts
|

The nonword-reading deficit of disabled readers: A developmental interpretation.

Abstract: This article presents empirical evidence challenging the received wisdom that a nonword-reading deficit is a characteristic trait of disabled readers. On the basis of 2 large-scale empirical studies using the reading-level match design, we argue that a nonword-reading deficit is the consequence of normal developmental differences in word-specific knowledge between disabled readers and younger normal readers (both groups being matched on real-word reading). The first study shows that the nonword-reading deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 104 publications
2
17
0
1
Order By: Relevance
“…Although this design is still used in some recent studies, it was formally proven that this method often entails methodological problems as it typically confounds diagnostic status with age (cf. Van den Broeck et al, 2010; Van den Broeck and Geudens, 2012; but see Zhou et al, 2014, for a notable exception in which a retrospective RLM-design is used comparing groups when they are at the same age).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this design is still used in some recent studies, it was formally proven that this method often entails methodological problems as it typically confounds diagnostic status with age (cf. Van den Broeck et al, 2010; Van den Broeck and Geudens, 2012; but see Zhou et al, 2014, for a notable exception in which a retrospective RLM-design is used comparing groups when they are at the same age).…”
Section: Introductionmentioning
confidence: 99%
“…However, Van den Broeck and Geudens (2012) have shown that a RLM design is likely to create processing deficit findings that may in fact be the result of the age differences between groups. One plausible scenario is that the group of older dyslexic readers reached the same reading score in the text reading test as the younger typical readers because they could rely on better word specific knowledge simply because they are older (for evidence see Van den Broeck et al, 2010). The younger normal readers on the other hand probably depended more on their decoding ability in order to reach the same performance level as the older dyslexic readers on the text reading task.…”
Section: Introductionmentioning
confidence: 99%
“…;Van den Broeck, Geudens, & van den Bos, 2010); otherwise participants in one group are compared with statistically extrapolated but nonexistent participants in another group, resulting in meaningless conclusions. For example, when no dyslexic readers are found in the upper tail of the distribution of Mean number of correctly recalled filler and Hebb items in the different conditions, for both typical and dyslexic readers.…”
mentioning
confidence: 99%
“…However, although there is abundant evidence that less‐skilled readers have deficits in reading nonwords, the causes of this impairment are not well understood (see e.g. Van den Broeck, Geudens & van den Bos, , for a recent discussion). For example, a prominent explanation for this effect is that low‐skill readers have a fundamental phonological deficit which impedes the acquisition of reliable GPC rules (Snowling, ).…”
Section: Reading Skill and The Nonword Deficitmentioning
confidence: 99%